Educational Marketing Management Strategy at Al-Azhar Islamic Junior High School Cairo Palembang - Yadi, M. Riandry; Suryana, Ermis; Maryamah, Maryamah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
Marketing in the context of educational services is a social and managerial process that aims to get what is needed and desired by creating offers and exchanging valuable products with other parties in the field of education. Marketing ethics in the world of education is to offer the quality of intellectual services and the formation of character as a whole. This is because education is complex and is carried out by the person responsible. The schooling results refer far to the future, fostering the lives of citizens and the next generation of scientists. Maintaining the existence and image of the school in the eyes of the public and customers of educational services amid the rapid competition is done by carrying out educational service marketing activities. In this regard, the educational marketing at Al Azhar Islamic Junior High School Cairo Palembang offers superior programs implemented in various extracurricular activities. The superior programs offered at Al Azhar Islamic Junior High School Cairo Palembang through this marketing activity to quickly be distributed to the community and customers of educational services, Al Azhar Islamic Junior High School Cairo Palembang has selected and established an effective marketing management strategy, namely word of mouth or mouth to mouth. The research results show that the marketing concept carried out at Al Azhar Islamic Junior High School Cairo Palembang is to offer superior programs using various strategies. Marketing activities carried out by implementing marketing strategies have turned out to have a positive impact that is quite significant. This is evident from the many enthusiasts from the community who obtain educational services for their children at Al Azhar Islamic Junior High School Cairo Palembang today.